2021
DOI: 10.3389/fmed.2021.629096
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Image Quality and Lesion Detectability With Digital PET/CT System

Abstract: Purpose: The aim of this study was to assess image quality and lesion detectability acquired with a digital Positron Emission Tomography/Computed Tomography (PET/CT) Siemens Biograph Vision 600 system.Material and Methods: Consecutive patients who underwent a FDG PET/CT during the first week of use of a digital PET/CT (Siemens Biograph Vision 600) at the nuclear medicine department of the university hospital of Brest were analyzed. PET were realized using list mode acquisition. For all patients, 4 datasets wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Some methods proposed to obtain high-resolution PET images include increasing the acquisition time, using a time-of-flight technique, new reconstruction methods, and semiconductor-based PET/CT scanners [ 13 , 14 , 15 ]. In addition, silicon photomultiplier (SiPM)-based detectors (in semiconductor-based PET/CT scanners) have several advantages compared with photomultiplier tubes, such as a smaller size, higher intrinsic time resolution, and higher photon detection efficiency [ 15 , 16 , 17 , 18 ]. Van Sluis et al reported that on semiconductor PET/CT images, the lesion demarcation was sharper, the overall image quality was higher, and the visually assessed signal-to-noise ratio was higher than on conventional PET/CT images [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some methods proposed to obtain high-resolution PET images include increasing the acquisition time, using a time-of-flight technique, new reconstruction methods, and semiconductor-based PET/CT scanners [ 13 , 14 , 15 ]. In addition, silicon photomultiplier (SiPM)-based detectors (in semiconductor-based PET/CT scanners) have several advantages compared with photomultiplier tubes, such as a smaller size, higher intrinsic time resolution, and higher photon detection efficiency [ 15 , 16 , 17 , 18 ]. Van Sluis et al reported that on semiconductor PET/CT images, the lesion demarcation was sharper, the overall image quality was higher, and the visually assessed signal-to-noise ratio was higher than on conventional PET/CT images [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the integration of a new type of detectors has allowed the development of so-called "digital" PET/CT scanners, replacing the classical "analog" PET/CT. Recent studies have shown an improvement of image quality and lesion detectability with a digital PET/CT system [19]. Thus, digital PET/CT will likely gradually replace analog PET/CT, making it necessary to evaluate radiomic models on this new generation of PET/CT.…”
Section: Introductionmentioning
confidence: 99%
“…18 F‐fludeoxyglucose ( 18 F‐FDG) PET is widely used to assess glucose metabolic information in primary tumors, lymph nodes, or distant metastases in oncological patients 5 . With the advent of novel digital PET scanner, the lesion detection capability shows an improvement, owing to the higher sensitivity and better spatial resolution compared to the traditional analog PET scanner 6,7 . However, the adverse impact of respiratory motion is more pronounced for PET scanners with a higher spatial resolution, highlighting the importance of motion correction by the digital system 8 .…”
Section: Introductionmentioning
confidence: 99%
“…5 With the advent of novel digital PET scanner, the lesion detection capability shows an improvement, owing to the higher sensitivity and better spatial resolution compared to the traditional analog PET scanner. 6,7 However, the adverse impact of respiratory motion is more pronounced for PET scanners with a higher spatial resolution, highlighting the importance of motion correction by the digital system. 8 The data-driven gating (DDG) technique, which provides respiratory-gated PET images for motion correction, has been commercially developed.…”
Section: Introductionmentioning
confidence: 99%